Formação de biofilme, multirresistência aos antimicrobianos e detecção de genes relacionados a produção de carbapenemases em espécies de Klebsiella, diagnosticadas por espectrometria de massas, isoladas de diferentes infecções clínicas em cães / - Paz, Patrik Junior de Lima [UNESP] (Repositório UNESP, 2026)
Klebsiella spp. are opportunistic bacteria pathogenic for humans and animals, especially Klebsiella pneumoniae, which is often associated with respiratory, genitourinary, and systemic infections in dogs and acquired in human hospitals, frequently resistant to conventional antimicrobials. In this scenario, biofilm formation, multidrug resistance to antimicrobials and genes related to carbapenemases production were investigated among 55 Klebsiella isolates obtained from diseased dogs. Identification by mass spectrometry (MALDI-TOF MS) revealed a predominance of K. pneumoniae (74.5%), followed by K. variicola (20%), K. aerogenes (3.6%), and K. oxytoca (1.8%). The most frequent infections were urinary (47.3%), reproductive (10.9%), and respiratory (9.1%), with no predilection for sex, but with a higher occurrence in adult and elderly animals. In vitro susceptibility testing revealed that chloranfenicol showed moderate efficacy (78.2%) against the isolates. In contrast, high multidrug resistance was observed among isolates (36.4%), mainly K. pneumoniae, particularly to fluoroquinolones (enrofloxacin 45.5% and levofloxacin 45.5%) and β-lactam derivatives (amoxicillin + clavulanic acid 38.2% and cephalosporins, i.e., cephalexin 45.5% and ceftriaxone 41.8%). Phenotypic and molecular detection identified the blaKPC gene in 1.8% (1/55), confirming the presence of carbapenemases in dogs from Brazil. Biofilm formation was identified in 100% of isolates. The high multidrug resistance of isolates, particularly K. pneumoniae, and genetic identification of blaKPC, reinforce the need of rational use of antimicrobials in animals, especially owing to close contact between humans and dogs, in addition to the need of continuous vigilance of bacterial resistance, an emergent and global issue in One Health perspective. The present study contributes to molecular identification of Klebsiella species, vigilance of multidrug resistance of K. pneumoniae, and biofilm formation in isolates recovered from diseased dogs.

Klebsiella spp. are opportunistic bacteria pathogenic for humans and animals, especially Klebsiella pneumoniae, which is often associated with respiratory, genitourinary, and systemic infections in dogs and acquired in human hospitals, frequently resistant to conventional antimicrobials. In this scenario, biofilm formation, multidrug resistance to antimicrobials and genes related to carbapenemases production were investigated among 55 Klebsiella isolates obtained from diseased dogs. Identification by mass spectrometry (MALDI-TOF MS) revealed a predominance of K. pneumoniae (74.5%), followed by K. variicola (20%), K. aerogenes (3.6%), and K. oxytoca (1.8%). The most frequent infections were urinary (47.3%), reproductive (10.9%), and respiratory (9.1%), with no predilection for sex, but with a higher occurrence in adult and elderly animals. In vitro susceptibility testing revealed that chloranfenicol showed moderate efficacy (78.2%) against the isolates. In contrast, high multidrug resistance was observed among isolates (36.4%), mainly K. pneumoniae, particularly to fluoroquinolones (enrofloxacin 45.5% and levofloxacin 45.5%) and β-lactam derivatives (amoxicillin + clavulanic acid 38.2% and cephalosporins, i.e., cephalexin 45.5% and ceftriaxone 41.8%). Phenotypic and molecular detection identified the blaKPC gene in 1.8% (1/55), confirming the presence of carbapenemases in dogs from Brazil. Biofilm formation was identified in 100% of isolates. The high multidrug resistance of isolates, particularly K. pneumoniae, and genetic identification of blaKPC, reinforce the need of rational use of antimicrobials in animals, especially owing to close contact between humans and dogs, in addition to the need of continuous vigilance of bacterial resistance, an emergent and global issue in One Health perspective. The present study contributes to molecular identification of Klebsiella species, vigilance of multidrug resistance of K. pneumoniae, and biofilm formation in isolates recovered from diseased dogs.
Formación de biopelículas, resistencia a múltiples fármacos e identificación de genes relacionados con la producción de carbapenemasas en especies de Klebsiella, diagnosticadas mediante espectrometría de masas, aisladas de perros enfermos
Keywords: Microbiologia veterinária; Multirresistência bacteriana; Animais de companhia; Bacteriologia; Companion animals; Klebsiella pneumoniae; Carbapenems